FOLFOX-4 Chemotherapy for Patients With Unresectable or Relapsed Peritoneal Pseudomyxoma. (20th June 2014) - Pietrantonio, Filippo; Maggi, Claudia; Fanetti, Giuseppe; Iacovelli, Roberto; Di Bartolomeo, Maria; Ricchini, Francesca; Deraco, Marcello; Perrone, Federica; Baratti, Dario; Kusamura, Shigeki; Tamborini, Elena; Castano, Alessandra; et al.
Abstract: Purpose: The standard treatment of peritoneal pseudomyxoma is based on cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy (HIPEC). The establishment of newer systemic treatments is an unmet clinical need for unresectable or relapsed peritoneal pseudomyxoma. The aim of our study was to assess the activity of chemotherapy with 5-fluorouracil and oxaliplatin (FOLFOX-4 regimen) in terms of response rate in this subset of patients. Materials and Methods: Patients were included in a single-center, observational study and treated with FOLFOX-4 administered every 2 weeks for up to 12 cycles or until progressive disease or unacceptable toxicity. Results: Twenty consecutive patients were reviewed from July 2011 to September 2013. Only partial responses were observed, with an objective response rate of 20%. Median progression-free survival and overall survival were 8 months and 26 months, respectively. Two patients were able to undergo laparotomy with complete cytoreduction and HIPEC in one case. Safety data for FOLFOX-4 were consistent with the literature. By means of a mutant enriched polymerase chain reaction, KRAS mutation was found in 16 of 19 cases (84%), and MGMT promoter methylation was found in 8 (42%, all KRAS mutant). Conclusion: FOLFOX-4 chemotherapy is tolerable and active in patients with peritoneal pseudomyxoma when disease is deemed unresectable or relapsed after peritonectomy and HIPEC. The identification of predictive biomarkers, such as KRAS for resistance to anti-epidermal growth factor receptor monoclonal antibodies and MGMT for response to temozolomide, is a priority for the development of evidence-based treatment strategies for peritoneal pseudomyxoma. Abstract : The authors conducted a single-center, prospective observational study of treatment with 5-fluorouracil and oxaliplatin (FOLFOX-4 regimen) in patients with unresectable or recurrent peritoneal pseudomyxoma of appendiceal origin. Results showed that FOLFOX-4 chemotherapy is tolerable and active in patients with peritoneal pseudomyxoma when disease is deemed unresectable or relapsed after peritonectomy and hyperthermic intraperitoneal chemotherapy.